Synthesis and characterization of innovative resveratrol nanobelt-like particles and assessment of their bioactivity, antioxidative and antibacterial properties - Tomić, Nina; Matić, Tamara; Filipović, Nenad; Mitić Ćulafić, Dragana; Boccaccini, Aldo R.; Stevanović, Magdalena M. (Journal of Biomaterials Applications, 2023)
Recently, many studies have shown various beneficial effects of polyphenol resveratrol (Res) on human health. The most important of these effects include cardioprotective, neuroprotective, anti-cancer, anti-inflammatory, osteoinductive, and anti-microbial effects. Resveratrol has cis and trans isoforms, with the trans isoform being more stable and biologically active. Despite the results of in vitro experiments, resveratrol has limited potential for application in vivo due to its poor water solubility, sensitivity to oxygen, light, and heat, rapid metabolism, and therefore low bioavailability. The possible solution to overcome these limitations could be the synthesis of resveratrol in nanoparticle form. Accordingly, in this study, we have developed a simple, green solvent/non-solvent physicochemical method to synthesize stable, uniform, carrier-free resveratrol nanobelt-like particles (ResNPs) for applications in tissue engineering. UV–visible spectroscopy (UV-Vis) was used to identify the trans isoform of ResNPs which remained stable for at least 63 days. The additional qualitative analysis was performed by Fourier transform infrared spectroscopy (FTIR), while X-ray diffraction (XRD) determined the monoclinic structure of resveratrol with a significant difference in the intensity of diffraction peaks between commercial and nano-belt form. The morphology of ResNPs was evaluated by optical microscopy and field-emission scanning electron microscope (FE-SEM) that revealed a uniform nanobelt-like structure with an individual thickness of less than 1 μm. Bioactivity was confirmed using Artemia salina in vivo toxicity assay, while 2,2–diphenyl-1-picrylhydrazylhydrate (DPPH) reduction assay showed the good antioxidative potential of concentrations of 100 μg/ml and lower. Microdilution assay on several reference strains and clinical isolates showed promising antibacterial potential on Staphylococci, with minimal inhibitory concentration (MIC) being 800 μg/ml. Bioactive glass-based scaffolds were coated with ResNPs and characterized to confirm coating potential. All of the above make these particles a promising bioactive, easy-to-handle component in various biomaterial formulations.
CRIS-Team Scopus Importer:2023-07-07
Keywords: antibacterial activity; antioxidative activity; bioactivity assay; nanoparticles; Resveratrol